English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

6 answers

i^15 = (i*i)^7 * i = (-1)^7 * i = -i = 0 - i

2007-01-09 02:21:55 · answer #1 · answered by Jerry P 6 · 1 0

i^15

i^2 = -1
i^15 = (i^2)x(i^2)x(i^2)x(i^2)x(i^2)x(i^2)x(i^2) x i
i^15= -1 x-1 x-1 x-1 x-1 x-1 x-1 x i
i^15= -1 x i
i^15 = -i
or in the full form requested,
i^15 = 0 - i
or
i^15 = 0 + (-1)i
(I think '-i' looks best)

2007-01-09 02:17:45 · answer #2 · answered by Dr Bob UK 3 · 1 0

i^15 = ( i ^12 )( i ^ 3 )

= 1 ( -i)

= - i

in standard form: 0 - i

2007-01-09 02:18:04 · answer #3 · answered by Ray 5 · 0 0

0 - i

2007-01-09 02:16:59 · answer #4 · answered by bequalming 5 · 0 0

we know that, i=sqrt(-1)
so(-1)^15 = -1
therefore i^15 = -1 = -1 + i0

2007-01-09 02:35:48 · answer #5 · answered by Anonymous · 0 0

i

2007-01-09 02:16:47 · answer #6 · answered by gebobs 6 · 0 0

fedest.com, questions and answers